Uma proposta para a coexistência de múltiplas Arquiteturas de Internet do Futuro - Gavazza, José Augusto Tagliassachi (Universidade Federal de São Carlos, 2020)
The current Internet architecture has been the same since the time of its creation and has undergone increments and modifications in its protocols to meet new demands that have been arising over time. As the resolution of all these issues is not easily solved with the addition of new functionalities or architectural modifications, proposals for the development of new Internet architectures started around the world. With several new Internet architectures being proposed, choosing a new Internet architecture to replace the current one becomes an extremely complex task. Thus, the emergence of a heterogeneous environment composed of multiple Internet architectures that allows the coexistence of new Future Internet Architectures, through the current network infrastructure, becomes a viable solution. Thereby, this work presents a proposal that enables the coexistence of multiple Internet Architectures on the current network infrastructure, in order to enable communication between entities of the same Internet architecture, enabling the emergence of the heterogeneous environment composed of multiple Internet architectures. To this end, this proposal defines the creation and joint operation of programmable switches implemented in P4 language, specific controllers for each Internet architecture supported by the proposal and a Control Protocol used to standardize the exchange of control messages, regardless of the architecture, thus enabling the exchange of traffic between entities of the same Future Internet Architectures, through the existing network infrastructure. To demonstrate this proposal, a proof of concept was implemented in a virtualized environment, where the Future Internet Architectures ETArch and NovaGenesis were chosen to be initially supported by the solution, as well as the IPv4 protocol. Finally, the proof of concept validation and tests related to the processing time of data and control packets were performed, where the independence of processing time was observed in relation to the size of a package of such an architecture as well as other performance information.
A proposal for the coexistence of multiple Future Internet Architectures
Keywords: Arquitetura de Internet do Futuro; Redes Definidas por Software; Linguagem de Processamento de Pacotes; Future Internet Architecture; Software Defined Networking; Packet Processing Language; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO